Hexaploid-bridged introgression broadens genetic diversity and enriches clubroot-resistance alleles in Brassica juncea - Wu, Yongzhi; Liao, Jingyan; Deng, Yinquan; Ce, Fuquan; Bai, Peng; Peng, Lisha; Zhang, Xingxing; Wan, Yi; Qian, Wei; Mei, Jiaqin (Frontiers in Plant Science, 2026)
IntroductionThe narrow genetic base of current Brassica juncea (AABB) has limited the genetic improvement of this crop.MethodsIn this study, we developed novel germplasm by crossing synthetic hexaploid bridge lines (AABBBB and AAAABB) with diploid progenitors B. rapa (AA) and B. nigra (BB), followed by successive selfing and marker-assisted selection.Results and DiscussionAlthough the F1 hybrids exhibited wide variation in fertility and morphology, these traits stabilized at levels comparable to current B. juncea by the F2 and F3 generations. Whole-genome resequencing confirmed that the new-type lines not only constitute a unique genetic group but also show a genomic shift toward the current B. juncea cluster in the F2 populations. Consequently, these new-type lines represent a significant new source of genetic diversity. As a practical application, we introgressed clubroot resistance from the European fodder turnip ECD04 (B. rapa) into B. juncea using the hexaploid bridge strategy coupled with MAS. Over four selection cycles (F2 to F5), the donor allele frequency surged from 31.3% to 54.4%, showing a strong negative correlation with disease severity (r = -0.98) and yielding highly resistant F5 lines.ConclusionsThis study demonstrates that the hexaploid bridge strategy enables rapid genetic base broadening and efficient trait improvement in B. juncea.